Race and ethnicity on MS presentation and disease course. (April 2020) - Amezcua, Lilyana; McCauley, Jacob L
Multiple sclerosis (MS) has a strong racial and ethnic component and disproportionately affects whites of European background. Recent incidence reports suggest an increasing rate of MS among African Americans compared with whites. Despite this recent increase in MS in African Americans, Hispanics and Asians are significantly less likely to develop MS than whites of European ancestry. MS-specific mortality trends demonstrate distinctive disparities by race/ethnicity and age, suggesting that there is an unequal burden of disease. Inequalities in health along with differences in clinical characteristics that may be genetic, environmental, and social in origin may be contributing to disease variability and be suggestive of endophenotypes. The overarching goal of this review was to summarize the current understanding on the variability of disease that we observe in selected racial and ethnic populations: Hispanics and African Americans. Future challenges will be to unravel the genetic, environmental, and social determinants of the observed racial/ethnic disparities.